TiO2/Chitosan-NH4I(+I-2)-BMII-based dye-sensitized solar cells with anthocyanin dyes extracted from black rice and red cabbage - Buraidah, M.H.; Teo, L.P.; Yusuf, S.N.F.; Noor, M.M.; Kufian, M.Z.; Careem, M.A.; Majid, Siti Rohana; Taha, R.M.; Arof, Abdul Kariem (Hindawi Publishing Corporation, 2011)
Dye sensitized solar cells (DSSCs) were fabricated using anthocyanin dye and polymer electrolyte with ammonium iodide (NH4I) salt. The study was designed to focus on increasing the efficiency of the DSSC. DSSC using 26.9 wt.% chitosan-22wt.% NH4I(+2.2 wt.% I-2)-48.9wt. % IL solid electrolyte, black rice anthocyanin with Pt counter electrode showed J(sc) of 172 mu A cm(-2) and V-oc of 195mV. The performance of the cell with Pt electrode was further improved by coating a blocking layer on the indium tin oxide (ITO) substrate. The black rice DSSC using 11wt. % (chitosan:PEO, wt. ratio 30: 70)-9wt. % NH4I-80wt. % BMII gel electrolyte exhibited J(sc) of 1213 mu A cm(-2), V-oc of 400mV, FF of 0.47, and eta of 0.23%. The red cabbage anthocyanin DSSC containing (phthaloyl chitosan-PEO)-NH4I-BMII gel electrolyte using tartaric acid to adjust the pH of anthocyanin solution showed the best performance with the fill factor of 0.39, J(sc) of 3503 mu A cm(-2), V-oc of 340mV, and an overall conversion efficiency of 0.46%.